Q-STEAM APPROACH; A NEW PARADIGM OF TEACHING BASED ON THE AL-QURAN - Muzakkir, Muzakkir; Zulnaidi, Hutkemri; Abd Rauf, Rose Amnah (Numeracy, 2026)
Integrated learning is a pedagogical approach that fosters students' creativity, critical thinking, and their ability to connect classroom knowledge with real-world contexts. Unlike traditional learning, which emphasizes rote memorization of theories and formulas, integrated learning promotes the meaningful association of concepts across subjects, encouraging both teachers and students to perceive the relevance of education to everyday life. When instruction is rooted in real-life problems, students are more likely to apply their knowledge in practical situations, thereby deepening understanding and retention. Project-Based Learning (PBL) offers an effective strategy to address student disengagement by encouraging active participation through problem-solving activities. The Quran—Science, Technology, Engineering, Art, and Mathematics (Q-STEAM) model is an integrative, PBL-based approach that merges the STEAM framework developed by Yakman with Quranic principles. The Quran, as the primary source of guidance for Muslims, is incorporated through verses that relate to either the problems being addressed, or the character traits cultivated during learning. Q-STEAM provides opportunities for students to develop critical thinking and problem-solving abilities while fostering a closer relationship with the Quran. This approach not only enhances academic competence but also nurtures Islamic character development. The model applies mathematics as a medium to integrate Quranic teachings—both to convey the Quran through mathematics and to understand mathematics through the Quran. Such a paradigm is essential in modern education to cultivate moral values, spiritual awareness, and social competencies. Ultimately, this approach equips students with 21st-century skills and supports the formation of ulul albab—individuals who are intellectually and spiritually grounded.